Attributing Excellence in Medicine The History of the Nobel Prize - Hansson, Nils; Halling, Thorsten; Fangerau, Heiner (Clio Medica, 2019)
Attributing Excellence in Medicine discusses the aura around the prestigious Nobel Prize in Physiology or Medicine. It analyzes the social processes and contingent factors leading to recognition and reputation in science and medicine. This volume will help the reader to better understand the dynamics of the attribution of excellence throughout the 20th century. Contributors are Massimiano Bucchi, Fabio De Sio, Jacalyn Duffin, Heiner Fangerau, Thorsten Halling, Nils Hansson, David S. Jones, Gustav Källstrand, Ulrich Koppitz, Pauline Mattsson, Katarina Nordqvist, Scott H. Podolsky, Thomas Schlich and Sven Widmalm.